Impacts of air pollutants from rural Chinese households under the rapid residential energy transition - Shen, Guofeng; Ru, Muye; Du, Wei; Zhu, Xi; Zhong, Qirui; Chen, Yilin; Shen, Huizhong; Yun, Xiao; Meng, Wenjun; Liu, Junfeng; Cheng, Hefa; Hu, Jianying; et al. (Nature communications, 2019)
Rural residential energy consumption in China is experiencing a rapid transition towards clean energy, nevertheless, solid fuel combustion remains an important emission source. Here we quantitatively evaluate the contribution of rural residential emissions to PM 2.5 (particulate matter with an aerodynamic diameter less than 2.5 μm) and the impacts on health and climate. The clean energy transitions result in remarkable reductions in the contributions to ambient PM 2.5 , avoiding 130,000 (90,000–160,000) premature deaths associated with PM 2.5 exposure. The climate forcing associated with this sector declines from 0.057 ± 0.016 W/m 2 in 1992 to 0.031 ± 0.008 W/m 2 in 2012. Despite this, the large remaining quantities of solid fuels still contributed 14 ± 10 μg/m 3 to population-weighted PM 2.5 in 2012, which comprises 21 ± 14% of the overall population-weighted PM 2.5 from all sources. Rural residential emissions affect not only rural but urban air quality, and the impacts are highly seasonal and location dependent. Residential solid fuel use constitutes a large amount of air pollution but has been gradually replaced by other cleaner energy during the past three decades. Here the authors investigated the contribution of rural residential sector to ambient PM 2.5 pollution and the resulting climate forcing and health impacts, and find that the remaining large quantities of solid fuels used in rural households are still a major contributor to ambient air pollution despite of decrease in its pollutant emissions and relative contribution to PM 2.5 due to the clean energy transition.